2019
DOI: 10.1589/jpts.31.170
|View full text |Cite
|
Sign up to set email alerts
|

A study on muscle activity based on the ankle posture for effective exercise with indoor horse riding machine

Abstract: [Purpose] Although much researches have been conducted on the hippotherapy, the intervention methods of the previous studies focus on the pelvis posture. Thus, this study analyzed the electromyogram (EMG) of trunk muscle and lower limb muscle to analyze the kinetic factors. Based on the analysis, this study aims to compare the muscle load and suggest effective exercise method. [Participants and Methods] This study checked the muscle activity of Rectus abdominis (RA), Erector spinae (ES), Rectus femoris (RF), A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, very few studies investigating electrical muscle activity and hippotherapy have been published in the scientific literature to date, with even less focusing on patients with CP. The few available studies address the findings from a qualitative point of view, with none carrying out a quantitative analysis of EMG signals from either the time or the frequency domains [18,[44][45][46][47]. We focused here on the electrical activity of muscle measured during dynamic postural balance while sitting through surface EMG.…”
Section: Discussionmentioning
confidence: 99%
“…However, very few studies investigating electrical muscle activity and hippotherapy have been published in the scientific literature to date, with even less focusing on patients with CP. The few available studies address the findings from a qualitative point of view, with none carrying out a quantitative analysis of EMG signals from either the time or the frequency domains [18,[44][45][46][47]. We focused here on the electrical activity of muscle measured during dynamic postural balance while sitting through surface EMG.…”
Section: Discussionmentioning
confidence: 99%
“…Items in both tests require lateral pelvic lifting, which involves activation and control of trunk, pelvic, and abdominal muscles that contribute to core stability [80]. Although most studies to date have measured flexor and extensor muscle activity [81][82][83][84][85], one study reported high magnitudes of muscle activity from the internal oblique abdominus in older non-riders [82] and another between novice and advanced jockeys [86], highlighting the involvement of other core stabilizers. Greater mediolateral amplitude and velocity of the center of pressure have been measured during riding in a group of cerebral palsy participants with five years of therapeutic riding experience compared to controls, also illustrating a deficit in mediolateral trunk control due to impairment [87].…”
Section: The Relationship Between Impairment and Performancementioning
confidence: 99%